Current Perspectives on Treatment of Gram-Positive Infections in India: What Is the Way Forward? - Atul P. Kulkarni; Vasant C. Nagvekar; Balaji Veeraraghavan; Anup R. Warrier; Deepak TS; Jaishid Ahdal; Rishi Jain (Interdisciplinary Perspectives on Infectious Diseases)
The emerging antimicrobial resistance leading to gram-positive infections (GPIs) is one of the major public health threats worldwide. GPIs caused by multidrug resistant bacteria can result in increased morbidity and mortality rates along with escalated treatment cost and hospitalisation stay. In India, GPIs, particularly methicillin-resistant Staphylococcus aureus (MRSA) prevalence among invasive S. aureus isolates, have been reported to increase exponentially from 29% in 2009 to 47% in 2014. Apart from MRSA, rising prevalence of vancomycin-resistant enterococci (VRE), which ranges from 1 to 9% in India, has raised concerns. Moreover, the overall mortality rate among patients with multidrug resistant GPIs in India is reported to be 10.8% and in ICU settings, the mortality rate is as high as 16%. Another challenge is the spectrum of adverse effects related to the safety and tolerability profile of the currently available drugs used against GPIs which further makes the management and treatment of these multidrug resistant organisms a complex task. Judicious prescription of antimicrobial agents, implementation of antibiotic stewardship programmes, and antibiotic policies in hospitals are essential to reduce the problem of drug-resistant infections in India. The most important step is development of newer antimicrobial agents with novel mechanisms of action and favourable pharmacokinetic profile. This review provides a synopsis about the current burden, treatment options, and the challenges faced by the clinicians in the management of GPIs such as MRSA, Quinolone-resistant Staphylococcus, VRE, and drug-resistant pneumococcus in India.